2010
DOI: 10.1007/s13258-009-0832-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of cathepsin F gene from olive flounder Paralichthys Olivaceus

Abstract: We isolated a homologue of cathepsin F from cDNA library of olive flounder liver. A 2,077 kb full-length cDNA encoding a predicted polypeptide of 474 amino acids was sequenced. The flounder cathepsin F exhibits a domain structure typical for papain-like cysteine proteases, a 17 amino acid N-terminal hydrophobic signal sequence followed by an extraordinarily long propeptide of 244 amino acids and the domain of the mature protease comprising 213 amino acids. The mature region contains all features characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In previous study, Kim et al ( 2010 ) reported cathepsin F that isolated from olive flounder liver cDNA library was evenly distributed all tissues in adult flounder and transcriptional level was gradually increased from 7 dph to 34 dph. But, Fabra & Cerdà ( 2004 ) described that cathepsin F mRNA was found throughout the oocyte growth or vitellogenesis period and a transient accumulation during oocyte maturation in teleost Fundulus heteroclitus .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In previous study, Kim et al ( 2010 ) reported cathepsin F that isolated from olive flounder liver cDNA library was evenly distributed all tissues in adult flounder and transcriptional level was gradually increased from 7 dph to 34 dph. But, Fabra & Cerdà ( 2004 ) described that cathepsin F mRNA was found throughout the oocyte growth or vitellogenesis period and a transient accumulation during oocyte maturation in teleost Fundulus heteroclitus .…”
Section: Resultsmentioning
confidence: 96%
“…The homologs search of the EST sequence with the corresponding amino acid sequence was examined using blast searches of Genbank and sequence alignment was performed with the CLUSTALW program ( ). A databank search showed that liver-1-D2 was revealed to be homologous with published flounder cathepsin F ( Kim et al, 2010 ) in olive flounder and has significant high identity above 98%. When compared to cathepsin F of other species were 98% with olive flounder (FJ436098.1), 91% with zebra mbuna (XP_004563245.1), 91% with nile tilapia (XP_003451852.1), 89% with marine medaka (AEA51106.1), 88% with atlantic salmon (ACN10907.1), 88% with ricefish (XP_004073613.1) and 87% with zebrafish (NP_001071036.1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations